2009
DOI: 10.1104/pp.109.144022
|View full text |Cite
|
Sign up to set email alerts
|

A WD40 Repeat Protein fromMedicago truncatulaIs Necessary for Tissue-Specific Anthocyanin and Proanthocyanidin Biosynthesis But Not for Trichome Development    

Abstract: WD40 repeat proteins regulate biosynthesis of anthocyanins, proanthocyanidins (PAs), and mucilage in the seed and the development of trichomes and root hairs. We have cloned and characterized a WD40 repeat protein gene from Medicago truncatula (MtWD40-1) via a retrotransposon-tagging approach. Deficiency of MtWD40-1 expression blocks accumulation of mucilage and a range of phenolic compounds, including PAs, epicatechin, other flavonoids, and benzoic acids, in the seed, reduces epicatechin levels without corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
156
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(170 citation statements)
references
References 72 publications
(95 reference statements)
8
156
0
Order By: Relevance
“…Previously, a WD40 repeat protein, orthologous to Arabidopsis TTG1, was identified in M. truncatula and called MtWD40-1 (15). M. truncatula wd40-1 mutants display a drastic decrease of soluble and insoluble PA (15). However, overexpression of MtWD40-1 in M. truncatula hairy roots results in an increase of anthocyanin concentration without affecting PA concentration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, a WD40 repeat protein, orthologous to Arabidopsis TTG1, was identified in M. truncatula and called MtWD40-1 (15). M. truncatula wd40-1 mutants display a drastic decrease of soluble and insoluble PA (15). However, overexpression of MtWD40-1 in M. truncatula hairy roots results in an increase of anthocyanin concentration without affecting PA concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, a WD40 repeat protein, orthologous to Arabidopsis TTG1, was identified in M. truncatula and called MtWD40-1 (15). M. truncatula wd40-1 mutants display a drastic decrease of soluble and insoluble PA (15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A WD-40 protein is a key component of the transcriptional complex that activates PA biosynthetic genes (Lepiniec et al, 2006;Pang et al, 2009), and we recently reported that the MYB transcription factor MtPAR (for proanthocyanidin regulator) can activate the promoter of M. truncatula WD40-1 in yeast (Saccharomyces cerevisiae; Verdier et al, 2012). To search for new positive regulators of WD40-1, which may also play a role in PA biosynthesis, we performed a yeast one-hybrid (Y1H) screen against a complementary DNA (cDNA) library of young seeds harvested at 10 d after pollination (DAP).…”
Section: Identification Of Mtmyb5 and Mtmyb14mentioning
confidence: 99%
“…affymetrix.com/estore/browse/products.jsp?productId=131507 #1_1, accessed 29 May 2013). Several studies in model legumes have employed these GeneChip Genome Arrays for research into developmental or metabolic pathways (Pang et al 2009;Verdier et al 2013). In the case of soybean, the GeneChip Soybean Genome Array permitted the characterisation of genome-wide expression patterns, and identified drought-responsive candidate genes.…”
Section: Hybridisation-based Gene Expression Profilingmentioning
confidence: 99%